Strategi Pembelajaran Online di Perguruan Tinggi pada Masa Pandemi Covid-19: (Studi Kasus pada Universitas Muhammadiyah Tangerang) - Indah Kusumawati (Neolectura, 2021)
In the COVID-19 pandemic, where all lines of human life were affected, we need to think of learning processes and strategies that can reduce face-to-face, where in this process we use online systems because they are more flexible and efficient in meeting learning needs, in related online models, utilization media, learning styles, and types of communication used by students, out of 150 students who were used as research samples from the Faculty of Economics at the Muhammadiyah University of Tangerang in the COVID-19 pandemic, the result was that 70% of the students of the Faculty of Economics at Muhammadiyah University in Tangerang were familiar with various patterns the learning. Students most like the learning system through WhatsApp and Google Classroom, in addition it needs further research to research on this online problem-based, collaborative, and other models.